2022
DOI: 10.1111/crj.13528
|View full text |Cite
|
Sign up to set email alerts
|

Objective physical activity level is associated with rectus femoris muscle echo‐intensity in patients with chronic obstructive pulmonary disease

Abstract: Introduction Skeletal muscle dysfunction is one of the major extrapulmonary complications of chronic obstructive pulmonary disease (COPD). Some studies have reported a relationship between physical activity (PA) level and skeletal muscle quality assessed by echo‐intensity (EI) in healthy individuals but not in patients with COPD. Objectives The aim of this study is to investigate the relationships between PA level and both skeletal muscle EI and skeletal muscle mass in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Although pulmonary rehabilitation, bronchodilators and anti-inflammatory agents provides the greatest improvement in dyspnea, exercise tolerance, and health-related quality of life, 25 it is very difficult to change physical activity and with poor outcome. 26 Therefore, COPD is a major heterogeneous disease and one of the world’s leading causes of death, and it is urgent for diagnostic and prognostic biomarkers for COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Although pulmonary rehabilitation, bronchodilators and anti-inflammatory agents provides the greatest improvement in dyspnea, exercise tolerance, and health-related quality of life, 25 it is very difficult to change physical activity and with poor outcome. 26 Therefore, COPD is a major heterogeneous disease and one of the world’s leading causes of death, and it is urgent for diagnostic and prognostic biomarkers for COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, EI is a practical method for assessing age-related risks associated with reduced muscle quality [9]. Okura et al found an inverse relationship between physical activity levels and rectus femoris EI in older adult patients [10].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It has become increasingly popular as an assessment tool to evaluate longitudinal changes in muscle characteristics and to evaluate intervention efficacy in relation to exercise, nutrition and/or pharmacological interventions targeting muscle in healthy and diverse patient populations. 1,[3][4][5][6] Current literature is focused on muscle ultrasound evaluation of the quadriceps muscle group due to its size and importance in physical function, with rectus femoris (RF) muscle thickness considered to be a reliable reflection of muscle strength. [7][8][9] Muscle ultrasound imaging has demonstrated good to excellent inter-and intra-rater reliability and strong criterion validity compared to histochemistry analyses on muscle biopsy in older adults, 10 individuals with myopathic disease, 11 and intensive care unit (ICU) survivors 6-12 months after discharge.…”
Section: Introductionmentioning
confidence: 99%